2009
DOI: 10.1161/circulationaha.108.793463
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Procedure-Related Adverse Events in Patients Receiving Implantable Cardioverter-Defibrillator Therapy

Abstract: were male, and 27% were female. Women were more likely to have a history of heart failure (81% versus 77%, PϽ0.01), worse New York Heart Association functional status (57% versus 50% in class III and IV, PϽ0.01), and nonischemic cardiomyopathy (44% versus 27%, PϽ0.01) and were more likely to receive biventricular ICDs (39% versus 34%, PϽ0.01). In unadjusted analyses, women were more likely to experience any adverse event (4.4% versus 3.3%, PϽ0.001) and major adverse events (2.0% versus 1.1%, PϽ0.001). In multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(117 citation statements)
references
References 31 publications
9
108
0
Order By: Relevance
“…Reports from large multicentre registries with predominantly patients with ischemic heart dis ease demonstrated an early complication rate varying from 3.3% to 11% during the hospital admission for ICD implantation (41,42). In the present study, the rates of infection, lead displacement and malfunction were not uncommon, with annual rates of 1.1%, 1.3% and 1.4%, respectively.…”
Section: Discussionsupporting
confidence: 46%
“…Reports from large multicentre registries with predominantly patients with ischemic heart dis ease demonstrated an early complication rate varying from 3.3% to 11% during the hospital admission for ICD implantation (41,42). In the present study, the rates of infection, lead displacement and malfunction were not uncommon, with annual rates of 1.1%, 1.3% and 1.4%, respectively.…”
Section: Discussionsupporting
confidence: 46%
“…35 In addition to women's older age and co-morbidities, smaller body size of females and a more challenging implantation procedure due to thinner right ventricular wall, smaller blood vessel diameter and a higher prevalence of anatomical variations in venoarterial relationships may explain such findings. 21,[35][36][37][38] On the other side, female gender seems associated with a better outcome after pacemaker placement, with males experiencing poorer survival following pacemaker implantation. 30,39 In conclusion, despite presenting to pacemaker implantation older, more symptomatic, with more co-morbidities, and experiencing more procedure-related complications, females seem to obtain a greater benefit from pacemaker implantation than males, with a lower long-term mortality.…”
Section: Permanent Pacemakersmentioning
confidence: 99%
“…On the contrary, no gender differences for pacemaker implantation have been documented in an Italian study (Boccia et al, 2005). A study from The Netherlands evaluating 33,564 patients demonstrated no gender differences in pacemaker selection, but a considerable drop in dual-chamber implantation with increasing age (Roeters et al, 2000). Another single centre study evaluating 259 patients found no significant difference in pacemaker mode selection between male and female patients (Veerareddy et al, 2007).…”
Section: Discussionmentioning
confidence: 99%